Social Interaction on Patients with Schizophrenia in Psychiatric Hospital - CECILIA INDRI KURNIASARI (Jurnal Ilmiah Kesehatan Keperawatan, 2019)
Social interaction is one of important indicator in the recovery process of mental patients, especially in patients with schizophrenia. Active social interactions can help patients with schizophrenia to socialize, while less active social interactions can cause social isolation to the risk of suicide. The purpose of this study was to determine the social interaction of patients with schizophrenia in psychiatric hospital. The number of participant in this study were 52 patients. Sampling with a purposive sampling technique. Data were collected using Social Interaction Questionnaire and Behavior Observation Sheet consisting of 18 statements. The analysis of this study was using univariate analysis with table of frequency distribution. The results showed that social interactions in schizophrenia patients were 45 patients with less active interacting categories, 5 patients with moderately active interacting categories, and 2 patients with active interacting categories. The results of the study can be used as a reference in determining appropriate nursing therapy in increasing social interaction in schizophrenia patients in mental hospitalsKeywords: social interaction; social psychological factors; schizophrenia;